Pengaruh Fasilitas Dan Harga Terhadap Kepuasan Pengunjung Di Daya Tarik Wisata Dempo Anai Land - Fauzi Alfiandri; Feri Ferdian (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
The issue discovery pertaining to amenities, costs, and visitor happiness is the driving force behind this. Quantitative research is one of the research types used. In this study, two different data kinds were used: primary and secondary. The study's participants were tourists who had visited Dempo Anai Land. One hundred customers were selected as the research sample using a non-probability selection technique. A Likert scale questionnaire that has undergone validity and reliability testing was used as the data gathering method. Data from the study were handled using SPSS 25.00. The research results shown that the facilities category in quite agree, namely 3.32, the price variable category in quite agree with 3.40 and the visitor satisfaction variable shows the quite agree category with a percentage of 3.36. As a result, the facility value (X1) has a significant and positive impact on visitor satisfaction (Y) with a beta or standardized coefficient of 0.501 with T count (6.468) and a significance of 0.000 <0.05. Similarly, the price research hypothesis (X2) has a significant and positive impact on visitor satisfaction (Y) with a beta or standardized coefficient of 0.352 with T count (2.026) and a significance of 0.000 <0.05. Furthermore, an Adjusted R Square value of 0.102 was obtained, showing that the impact of the facility variables (X1) and price (X2) on the visitor satisfaction variable (Y) was 10.2%, while 89.8% was influenced by other factors.